Morphological Characterisation, Molecular Subtyping And Phylogeny Of Blastocystis Sp. Isolated From Turkey (Meleagris Gallopavo) In Penang, Malaysia - Naser, Siti Alawiyah Jamal Abdul (2022)
Most poultry farms in Malaysia preferred rearing chickens either for eggs or/and meat than turkeys. This is due to several challenges such as parasitic load and heat stress in rearing turkey. Blastocystis is one of the most common protozoan parasites infecting poultry. As no study was conducted on study of Blastocystis infection in turkey in Malaysia, this study aims to determine the current status, the morphological characteristics and subtyping of Blastocystis from turkey reared either in closed house or free-range system in Penang, Malaysia. It was found that the prevalence of Blastocystis sp. infection in turkeys were moderately high with 41.6% (25/60) in the closed house and 45.0% (45/100) in free-range system as infection was higher in the female turkeys with no gastrointestinal signs and symptoms. Vacuolar form was the most common form found in the in vitro culture ranged between 5 to 20 μm in diameter with a rough surface coat and undulating cell surface viewed under the scanning electron microscope. Meanwhile, the ultrastructure of the cells from turkey isolates were varies with partially expanded electron-opaque vacuoles to electron-dense in fully distended vacuoles. Interestingly, the sequence analysis of 30 positive Blastocystis isolates from turkeys revealed one ST and three alleles namely, ST7 allele 99 (73.4%, n=22), ST7 allele 100 (23.3%, n=7) and ST7 allele 101 (3.3%, n=1). This was the first study to evaluate the prevalence, morphological and ST of Blastocystis sp. isolated from free-range and close house turkeys in Malaysia